New blocks for the same old joints. Issue 5 (October 2018) - Sinha, Sanjay K.; Suter, Shivani
Abstract : Purpose of review: New block techniques are being constantly developed or old techniques modified to improve outcomes after surgery. This review discusses the reasons why new block techniques need to be developed to match the needs of contemporary anesthetic practice. Recent findings: New block techniques have been developed for joint surgeries of both upper and lower extremities. New upper extremity blocks focus on decreasing the risk of complications like diaphragmatic paresis and improving the quality of blocks. Techniques for lower extremity surgeries are being performed distally, closer to the joints, to minimize weakness of the extremity. A review of the available evidence for these techniques is undertaken to get an understanding of the indications and limitations of these techniques. Summary: Future studies need to be undertaken to further refine these techniques and produce evidence of support for analgesic efficacy, safety, and reliability.